1990
DOI: 10.1177/153857449002400801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ticlopidine on Graft Patency Following Arterial Reconstructive Surgery in the Lower Extremity: A Multicenter Three-Year Prospective Study

Abstract: A multicenter, randomized, prospective trial was conducted to determine the clinical efficacy of ticlopidine, an antiplatelet agent, in the prevention of graft occlusion following vascular reconstructive surgery of the lower extremity for arteriosclerosis obliterans. Ticlopidine was administered for two years to one group of patients (112 reconstructed arterial segments) while a control group received no antithrombotic therapy (108 segments). There was no significant difference between the treated and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Two controlled trials of the platelet inhibitor, ticlopidine, in peripheral bypass grafts have been reported ( Table 2). The open, controlled trial 25 showed treatment bene®t only in a subgroup of patients with hyperlipidaemia and not overall or in a number of other subgroups analysed. The second trial published 26 had a multicentre, double-blind, placebocontrolled design and showed a signi®cant treatment bene®t up to 2 years in terms of graft patency, whether analysed by life-table techniques or by ITT analysis of patients alive with primary or secondary graft patency.…”
Section: Ticlopidinementioning
confidence: 96%
“…Two controlled trials of the platelet inhibitor, ticlopidine, in peripheral bypass grafts have been reported ( Table 2). The open, controlled trial 25 showed treatment bene®t only in a subgroup of patients with hyperlipidaemia and not overall or in a number of other subgroups analysed. The second trial published 26 had a multicentre, double-blind, placebocontrolled design and showed a signi®cant treatment bene®t up to 2 years in terms of graft patency, whether analysed by life-table techniques or by ITT analysis of patients alive with primary or secondary graft patency.…”
Section: Ticlopidinementioning
confidence: 96%